In search of the architectural design characteristics of coastal resort tourism in Terengganu / Izzati Zainal Abidin ... [et al.] - Zainal Abidin, Izzati; Ismail, Sumarni; Ismail, Nor'atiah; May Ling, Siow (2022)
Terengganu can adapt and consolidate to form its own character because of its commercial and cultural ties with its neighbors. It is recognised as the cradle of Malay culture, and the ability to adapt has enhanced the country's uniqueness and identity. However, indigenous cultures are believed to be losing their identity as globalization continues to advance. As a result of these issues, resort architecture is immediately rejected as a cheap knockoff that fails to reflect authentic regional values. One of the 2030 Sustainable Development Goals (SDGs) is to make human settlements inclusive, safe, resilient, and sustainable. Hence, the lack of research into the holistic tourist experience, particularly in the area of the integration of cultural influence, was the driving force behind the present study, which involved searching for the architectural design characteristics of coastal resorts that had been implemented to create each resort's identity. Therefore, this study aimed to identify characteristics of traditional Malay architectural identity in coastal resort tourism, based on a critical investigation of past studies and academic journals. To achieve this aim, the objectives of this study were to investigate the research gaps involving the planning and design aspects of coastal resorts, specifically in terms of the building placement, layout, and materials, as well as the integration of cultural identity, in the coastal resorts of the East Coast of Peninsular Malaysian. A systematic literature review (SLR) was conducted, and a total of 12 articles were taken into consideration. Thus, the findings also support the contention of the authors that there has been a lack of proactive research to establish how cultural identity features could be incorporated into resort architecture in the present while conforming to the pressure of twenty-first-century design constraints.